1008. Disease Severity Impact on Long-Term Virologic Response to Ibalizumab in Expanded Access Protocol (TMB-311). (31st December 2020) - Kumar, Princy; Leider, Jason; Slim, Jihad; Moyle, Graeme; Leonard, Maurice; Cash, R Brandon; Weinheimer, Steven; Mesquita, Pedro
Abstract: Background: The principal goal of antiretroviral therapy (ART) is durable suppression of HIV RNA. In treatment-experienced (TE) patients, ongoing viremia can lead to further accumulation of drug resistance, increased morbidity and mortality. ART efficacy often depends on HIV disease severity; therefore, we sought to assess its impact on long-term virologic suppression in patients treated with Ibalizumab (IBA), the first long-acting, post-attachment inhibitor approved for multi-drug resistant (MDR) HIV-1 treatment. Methods: In TMB-301, a Phase 3 study, 40 TE patients with viral load (VL) >1000 copies/mL (c/mL) received an intravenous (IV) loading dose of IBA (2000mg) followed by maintenance doses (800mg IV) every 2 weeks combined with an optimized background regimen. Patients who completed TMB-301 in the US (n=27) continued to an expanded access protocol TMB-311. To determine the impact of baseline (BL) disease on long-term virologic response, we conducted an on-treatment analysis stratified by BL VL and CD4 count up to week 96. Differences in the proportion of suppressed (< 50 c/mL) individuals among the strata were assessed by Fisher's exact test. Results: Median BL VL and CD4 count were 35, 350 c/mL and 73 cells/mL, respectively. The number of patients in the VL strata were 11, 17 and 12 for VL < 10, 000, 10, 000-70, 000, and >70, 000 c/mL, respectively. There were 12, 10, 5 and 13 patients in the subgroups with CD4 count < 10, 10-100, >100-200 and >200 cells/µL. Population disease severity was reflected by four deaths (unrelated to study drug). Overall, the proportion of suppressed patients increased from 55% at week 24 (n=31) to 75% for patients remaining on treatment for 96 weeks (n=20). Median VL decrease was 2.9 log10 c/mL. Notably, no statistically significant differences were found across groups. Among patients with advanced HIV disease, 66.7% with CD4 count < 10 cells/mL and 71.4% with VL >70, 000 c/mL at BL remained fully suppressed at week 96. Conclusion: In TE patients with advanced HIV disease, maximal viral suppression with IBA was observed regardless of BL CD4 or VL strata if patients remained on treatment. This demonstrates that TE patients across the spectrum of HIV disease, can achieve viral suppression by using drugs with a new mechanism of action. Disclosures: Princy Kumar, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Jason Leider, MD, PhD, THERA (Speaker's Bureau) Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau) Graeme Moyle, MD, Theratechnologies (Consultant) Maurice Leonard, PhD, Theratechnologies Europe Ltd (Employee, Shareholder) R Brandon Cash, PharmD, Theratechnologies (Employee) Steven Weinheimer, PhD, TaiMed Biologics USA (Employee) Pedro Mesquita, PhD, Theratechnologies, Inc. (Employee)